Encapsulation of individual living cells with enzyme responsive polymer nanoshell. (March 2019) - Yang, Jianmin; Yang, Yingjun; Kawazoe, Naoki; Chen, Guoping
Abstract: Cell delivery in cell therapy is typically challenged by the low cell survival rate and immunological rejection during cells injection and circulation. Encapsulation of cells with semipermeable hydrogels or membranes can improve cell viability by resisting high shear force and inhibit immune response with the physical isolation effect. Herein, the individual HeLa cells and human mesenchymal stem cells (hMSCs) were encapsulated with enzyme responsive polymer nanoshell. The encapsulation shell was prepared via the Layer-by-Layer (LbL) assembly of functionalized gelatin and click chemistry of peptide linker and gelatin. The encapsulated cells showed high cell viability and could resist the physical stress. Moreover, the encapsulation shell had a prolonged encapsulation sustaining period and could effectively prevent the invasion of external entities. In addition, on-site cell release was realized via enzymolysis of the encapsulation shell by human matrix metalloproteinase-7 (MMP-7), an overexpressed enzyme on tumor area. The finding of this study proved a potential approach in cell therapy, especially for cell-based cancer therapy.